The Study of Everyday Life’s Practices of Muslim Teenagers In Deep South of Thailand - Sukka, Vilasinee; Maliwan, Ekarach; Kullawong, Manassawas (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2020)
Previously, the study of identity of Muslim teenagers in the three southern border provinces had been focused on a stigmatization and a deviation of Muslim teenager from the traditions or conventional term of religious practices. Many studies are focus to answer the question of who the Muslim is, what are the social, cultural characteristics of them and how to practice the religion properly. Therefore, this kind of the study on Muslim society and culture creates a stagnant and has a ready-made answer. Hence, this article aims to highlight the importance of research on Muslims in Thai society, especially the study of identity through Muslim teenager by employing de Certeau's Practice of Everyday Life. The documentary analysis have been used in order to analyze and formulate a conceptual framework for understanding Muslim adolescents in terms of ideas, the meaning, the feeling, including their daily lives. The importance of this concept is offering an analysis of Muslim teenager’s agency as well as it also provides an idea of how they negotiate with traditional culture and social change and current culture.